Autonomic pathophysiology in heart failure patients. Sympathetic-cholinergic interrelations. - Porter, T R (1990)
We conducted this study in an effort to characterize and understand vagal abnormalities in heart failure patients whose sympathetic activity is known. We measured sympathetic (peroneal nerve muscle sympathetic recordings and antecubital vein plasma norepinephrine levels) and vagal (R-R intervals and their standard deviations) activities in eight heart failure patients and eight age-matched healthy volunteers, before and after parasympathomimetic and parasympatholytic intravenous doses of atropine sulfate. At rest, sympathetic and parasympathetic outflows were related reciprocally: heart failure patients had high sympathetic and low parasympathetic outflows, and healthy subjects had low sympathetic and high parasympathetic outflows. Low dose atropine, which is known to increase the activity of central vagal-cardiac motoneurons, significantly increased R-R intervals in healthy subjects, but did not alter R-R intervals in heart failure patients. Thus, our data document reciprocal supranormal sympathetic and subnormal parasympathetic outflows in heart failure patients and suggest that these abnormalities result in part from abnormalities within the central nervous system.